Successful treatment of arrhythmia-induced cardiomyopathy in an infant with tuberous sclerosis complex. Issue 1 (December 2016) - Motoki, Noriko; Inaba, Yuji; Matsuzaki, Satoshi; Akazawa, Yohei; Nishimura, Takafumi; Fukuyama, Tetsuhiro; Koike, Kenichi
Abstract Background Tuberous sclerosis complex (TSC) is an autosomal-dominant tumor suppressor gene syndrome that is characterized by the development of distinctive benign tumors and malformations in multiple organ systems (N Eng J Med 355:1345-1356, 2006). Cardiac rhabdomyomas are intracavitary or intramural tumors observed in 50–70 % of infants with TSC but only cause serious clinical problems in a very small fraction of these patients (N Eng J Med 355:1345-1356, 2006; Pediatrics 118:1146-1151, 2006; Eur J Pediatr 153:155-7, 1994); most individuals have no clinical symptoms and their tumors spontaneously regress. However, despite being clinically silent, these lesions can provoke arrhythmias and heart failure (Pediatrics 118:1146-1151, 2006; Eur J Pediatr 153:155-7, 1994). Case presentation We here report the clinical findings of an infant suffering from TSC complicated with dilated cardiomyopathy (DCM) after the regression of cardiac rhabdomyomas. Although his tumors improved spontaneously, tachycardia and irregular heart rate due to frequent premature ventricular and supraventricular contractions persisted from the newborn period and were refractory to several medications. His cardiomyopathy was suspected to have been induced by the tachycardia or arrhythmia. We found carvedilol therapy to be safe and highly effective in treating the cardiomyopathy. To our knowledge, this is the first case report of TSC with DCM after regression of cardiac tumors and its successful treatment. Conclusion The patient's clinical course suggests that careful life-long disease management is important, even in TSC patients without apparent symptoms.